Emerging Biosorption, Adsorption,Ion Exchange, and Membrane Technologies - Chen, J.Paul; Wang, Lawrence K.; Lei, Yang; Soh-Fong, Lim (Humana Press, 2007)
In the last 20 yr, the water industry has been faced with a series of great challenges. Industries have discharged wastewater that contains various new compounds. In addition, the demand for high-quality water has been significantly increasing. As a result, new water treatment technologies have been developed. In this chapter, three novel technologies are introduced. The emerging technologies for the removal of heavy metals, disinfection byproducts, total organic carbons (TOC), and arsenic are illustrated.